stgenreg: A Stata Package for General Parametric Survival Analysis - Crowther, Michael J.; Lambert, Paul C. (Journal of Statistical Software, 2013)
In this paper we present the Stata package stgenreg for the parametric analysis of survival data. Any user-defined hazard function can be specified, with the model estimated using maximum likelihood utilising numerical quadrature. Models that can be fitted range from the Weibull proportional hazards model to the generalized gamma model, mixture models, cure rate models, accelerated failure time models and relative survival models. We illustrate the features of stgenreg through application to a cohort of women diagnosed with breast cancer with outcome all-cause death.